Aprender ortografia: análise do impacto da instrução e construção de práticas - Michelle Nogueira Lara Prado (2023)
Several spelling difficulties have been found in final grades elementary school (COUTO and OLIVEIRA, 2020; CASTRO, 2022). Graham, Harris and Chorzempa (2002) show, in their studies, that difficulties with spelling can potentially effect writing in several ways like: blur the message that an author is trying to convey; worse qualification in relation to the organization of the text's ideas, by the teachers when they read it; forgetfulness, by the student, of the ideas’ sequence in the text; embarrassment of students, who start to avoid writing. Given this evidence, we present the general objective of this research: to investigate which instructions are most effective for teaching and learning spelling and the impact of this teaching on the spelling of individual words and on the text production. As a methodology we will use action research, according to (PAIVA, 2019), interventionist and, at the same time, descriptive and a mixed scientific approach, with qualitative and quantitative methods for data collection. From the first data collection, in October 2021, a corpus was generated consisting of 92 text productions and 92 dictations, with 40 words each, collected in three 6th grade classes, from a municipal school in Belo Horizonte. The data were organized in an excel database and categorized according to Miranda (2020). Error analysis showed that phonological and orthographic categories predominate in the corpus. Then, based on this result, three different types of practices were built, two with direct and explicit instructions for teaching spelling and one with instructions aimed at studying the text, not directed at teaching spelling: 1) Direct - elaborated from groups of words and individual words; 2) Contextual - prepared from texts of various genres and with a degree of complexity appropriate to the school grade; 3) Spontaneist - reading and interpreting texts without specific guidelines on spelling writing. Each of these practices was applied in one of the classes participating in the research, from April to September 2022. At the end of this step, a new data collection was carried out, generating a new corpus with the same number of productions and dictations as the first collection. These data were also organized in an excel database and categorized according to Miranda (2020). Error analysis showed that all classes had a reduction in the number of errors both in production and in dictation, comparing the first with the second collection. Then, the statistical test was applied, the result found no statistically significant difference between the results of the three practices undertaken. However, a qualitative analysis of the results of this research revealed that teaching spelling for the 6th grade of Elementary School II is necessary and should happen through diversified practices, with direct and reflective instructions, since the students participating in this study improved spelling in individual words and in texts production. The different practices carried out in the three groups of different students showed what the authors Morais (2003), Nóbrega (2013), Treiman and Kessler (2014), Soares (2018) suggest for teaching spelling, that is, a systematic and reflective, built from the students' difficulties. In addition, the practices carried out point to possibilities for exploring Portuguese orthography aspects in the classroom, giving visibility to what can actually be done in the school reality.